Kabale University E-Learning Policy - Kabale University (2022)
The main objective of this policy is to enable and facilitate teaching and learning at Kabale University through electronic means. Specifically, it aims to provide a framework in which elearning can take place as a legitimate form of learning at the university, to guide the university’s investments to establish and use e-learning resources, and to provide for the training of teachers and learners in the appropriate use of such resources to achieve the expected course outcomes.